Workload Measurements in the EDEN ISS Greenhouse during the 2021 Antarctic Overwintering Mission - Zeidler, Conrad; Bunchek, Jess (2023)
From January 2018 to February 2022, the EDEN ISS project investigated technologies for plant cultivation and operation procedures for planetary surface greenhouses. The EDEN ISS space analog test facility was located near the German Neumayer Station III in Antarctica. For the fourth and final overwintering expedition from 2021 to early 2022, a tenth person joined the Neumayer Station III overwintering team as the dedicated on-site operator of the EDEN ISS greenhouse, supported by an interagency collaboration between DLR and NASA. For this final mission of the EDEN ISS Antarctic campaign, 790 g/m2/day fresh produce was grown within the 12.5 m2 plant cultivation area of the EDEN ISS greenhouse – comparable to production in prior missions. As in previous years, operator workload was assessed using the NASA Task Load Index to investigate which tasks/procedures could be facilitated in terms of workload, how workload changed over the course of the mission, and how workload could be reduced in the future. In this paper, we present the results of the NASA Task Load Index measurements conducted from 4 October 2021 to 26 December 2021. Detailed workload measurements are presented with respect to specific recurring tasks, e.g., daily/weekly/monthly routines, harvesting, and pruning, as well as workload on a daily, weekly, and monthly basis. The measurements show that there is a need to reduce the workload of the on-site operator in a space analog greenhouse. These studies provide valuable insight for operating future greenhouses on the Moon and Mars, which should already be included in the planning phases of such space missions.